Off-label drugs in palliative care: a Group Delphi treatment recommendation process. Issue 2 (12th May 2020) - Remi, Constanze; Weingärtner, Kathrin; Hagemann, Vera; Bausewein, Claudia; Hodiamont, Farina
Abstract : Objectives: The use of drugs beyond their marketing authorisation, that is, off-label use, is common practice in palliative care with over 70% of off-label use having little or no scientific support. The lack of evidence makes recommendations for off-label use essential, in order to increase the safety of drug therapy and thus patient safety. The aim of this study was to develop a guide for preparing and consenting drug-specific recommendations for off-label use in palliative care. Methods: Group Delphi Study with three rounds and a prior online survey to identify topics of dissent. Participants represented professional groups working in palliative care involved in direct patient care and/or drug management and various care settings. Furthermore, representatives of relevant professional associations, experts with academic, non-clinical background and experts with international expertise were invited. Results: 18/20 invited professionals participated in the prior online-survey. 15 experts participated in the Group Delphi process. Six domains, including identification of drugs, drug uses, assessment of evidence, formulation, consensus and updating of recommendations were generated and respective statements were included in the Group Delphi process. The consensus process resulted in 28 statements forming the guide for recommendations. Conclusions: The resultant systematic approach for preparing and consenting drug-specific recommendations for off-label use will allow the development of recommendations with transparent and reproducible monographs. This will help to increase treatment quality and patient safety as well as security of decision-making in palliative care. The developed guide is part of a larger project aiming to provide therapy recommendations for areas that have little or no scientific evidence.